Infrared plasmonic photodetectors: the emergence of high photon yield toroidal metadevices. (December 2019) - Gerislioglu, B.; Ahmadivand, A.; Adam, J.
Abstract: Plasmon excitations in metallic nanostructures can decay directly into dynamic electron–hole pairs, exploitable for photocurrent generation. This approach has extensively been employed to develop nanoplasmonic light-sensing devices with significant responsivity and quantum efficiency. Among the devices, infrared plasmonic photodetectors have gained particular interest for their wide range of technological applications, including spectroscopy, biosensing, and surveillance. This Review discusses the fundamentals, recent advances, and trending mechanisms in the understanding and applications of plasmon-enhanced photocurrent generation in nanostructures across the infrared spectrum. By highlighting and comparing the developed techniques, we demonstrate the newly introduced directions toward achieving high photon yield infrared plasmonic photodetection tools. As a promising concept in modern metaphotonics, we present the emergence of toroidal meta-atoms as plasmon-induced carrier generators with unconventionally exquisite properties for designing advanced, rapid, and next-generation plasmonic photodetectors with significantly high responsivity and photocurrent. Graphical abstract: Image 1 Highlights: The fundamentals, recent advances, and trending mechanisms in near-infrared detection are discussed. The novel approaches for the plasmon-enhanced photocurrent generation in nanostructures are highlighted. Several techniques are reviewed and new directions toward achieving high photon yield photodetection are summarized. Plasmonic toroidal metaphotodetectors are introduced as advanced light sensing platforms. The roadmap and future of the near-infrared plasmonic photodetection are explained.